Brief Guide : National Gallery of Art. - National Gallery of Art, Washington (Washington : National Gallery of Art, 1981)
The Collections: Florentine and Central Italian Art ; Venetian and North Italian Art ; Italian Art of the 17th and 18th Centuries ; Flemish and German Art ; Dutch Art ; Spanish Art ; French Art of the 17th, 18th, and Early 19th Centuries ; British Art ; American Art ; French Art of the 19th Century ; 20th Century Art ; Decorative Arts ; Prints and Drawings ; Index of American Design
Engels
boek